Bahasa Arab Al-Qur’an: Kajian Linguistik, Keistimewaan Bahasa, dan Implikasinya dalam Kajian Tafsir Al-Qur’an - Widodo, Arif (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
This study examines the linguistic characteristics, distinctive features, and exegetical implications of Qur’anic Arabic through a qualitative library research approach. The research is motivated by the existing gap between modern Arabic linguistic studies and Qur’anic exegesis, which are often treated as separate disciplines. By employing textual analysis and qualitative content analysis, this study analyzes selected Qur’anic verses across four linguistic levels: phonology, morphology, syntax, and semantics. The data consist of the Qur’an as the primary source, supported by classical tafsir works and contemporary linguistic literature published between 2000 and 2025. The study applies systematic literature selection with defined inclusion and exclusion criteria to ensure academic rigor.The findings reveal that Qur’anic Arabic exhibits a highly structured and consistent linguistic system characterized by phonological harmony, morphological precision, syntactic flexibility, and semantic depth. These features contribute to the concept of i‘jāz lughawī (linguistic inimitability), which distinguishes the Qur’an from other forms of Arabic discourse. The analysis also demonstrates that even minor linguistic variations—such as word forms, syntactic arrangements, and semantic nuances—have significant implications for interpreting Qur’anic meanings. Consequently, linguistic competence in classical Arabic is essential for accurate and comprehensive Qur’anic exegesis. This study concludes that integrating linguistic analysis with tafsir methodology is not only necessary but also epistemologically significant in contemporary Qur’anic studies. Such an interdisciplinary approach bridges the gap between structural linguistic analysis and interpretative understanding, thereby enhancing the accuracy and depth of Qur’anic interpretation. The study contributes to the development of a more systematic framework for integrating Arabic linguistics into Qur’anic exegesis and highlights its relevance for Islamic scholarship and Arabic language education